PHYSICAL TRAINING IN THE REHABILITATION AND PREVENTION IN PATIENTS WITH ISCHEMIC HEART DISEASE AFTER PERCUTANEOUS CORONARY INTERVENTIONS: THE BORDERS OF EFFICIENCY AND SAFETY - N. P. Lyamina; E. S. Karpova; E. V. Kotelnikova; E. A. Bizyaeva (Российский кардиологический журнал)
Currently, it is proved that physical training (FT) should be a compulsory component of programmes for complex rehabilitation of patients with coronary heart disease after PCI. However, given the heterogeneity of clinical status of patients after conducting PCI medical rehabilitation should be personalized as for the choice of intensity and exposure of FT and with obligatory monitoring of their effectiveness and safety. This greatly extends the possibilities of wide use of FT at the stage of rehabilitation in the real clinical practice.